Analisis Kemampuan Literasi Sains Mahasiswa Pendidikan Kimia di Universitas Tanjungpura - Tiya Ruslina Putri; Masriani Masriani*; Rahmat Rasmawan; Hairida Hairida; Erlina Erlina (JIPI (Jurnal IPA dan Pembelajaran IPA), 2022)
A prospective teacher needs have to qualified scientific literacy skills so that students have good abilities in learning science-related knowledge. However, assessments to measure students' scientific literacy skills that are adapted to PISA aspects are also still rarely carried out. Therefore, describing the scientific literacy ability of Chemical Education students at Tanjungpura University are needed. This research used quantitative descriptive method which aimed to describe students' scientific literacy skills. The sampling technique used is a saturated or full sampling technique which is samples are taken from all members of the population. The subjects of this study were students of Chemistry Education at Tanjungpura University as many as 45 students. Data collection techniques in this study are direct measurement and communication techniques. The measurement technique is done by giving a test in the form of three essay questions. Direct communication techniques in the form of semi-structured interviews to support research data and confirm student answers. Data collection tools in this research were scientific literacy tests and semi-structured interviews. The data were analyzed by providing a score of the results of the scientific literacy test, calculating the average test score, and determining the category of scientific literacy. Based on the results of data analysis, students' scientific literacy skills with an average percentage of content knowledge with competence in identifying scientific questions of 39.62%, procedural knowledge with competence to explain scientific phenomena by 26.38%, and epistemic knowledge with competence in using scientific evidence by 23.33%